Hubungan Sedentary Behavior Dengan Index Massa Tubuh Mahasiswa Pendidikan Jasmani Universitas Galuh - Wandi Haeruman; Gani Kardani; Asep Ridwan Kurniawan; Mohamad Rezha (Universitas Galuh, 2026)
This study aims to examine the relationship between sedentary behavior and body mass index (BMI) among students of the Physical Education Study Program at Galuh University. The background of this research is the high level of passive activities among students, such as prolonged sitting and low physical activity, which may affect their nutritional status and overall health. This is a quantitative correlational study using a cross-sectional design. The sample consisted of 100 respondents out of a total population of 120 active students from the 2022–2024 cohorts, selected through random sampling and calculated using the Slovin formula. Data were collected using the Sedentary Behavior Questionnaire (SBQ) and by measuring weight and height to calculate BMI. Data analysis was performed using the Pearson Chi-Square test with SPSS version 30.00. The results show that most students (70%) had a high level of sedentary behavior and were categorized as overweight (BMI > 25). Statistical analysis revealed a significant relationship between sedentary behavior and body mass index, with a p-value of 0.004 (< 0.05). Based on these findings, it can be concluded that sedentary behavior is significantly associated with increased body mass index in students. This research is expected to serve as a foundation for health education and lifestyle interventions among university students to prevent obesity.ABSTRAKPenelitian ini bertujuan guna untuk mengidentifikasi keterkaitan antara sedentary (gaya hidup menetap) dengan status gizi (index massa tubuh) Mahasiswa Penjas Universitas Galuh. Metodologi yang digunakan dalam penelitian ini adalah korelasional dengan menggunakan design cross sectional. Populasi pada penelitian ini adalah mahasiswa program studi pendidikan jasmani universitas galuh yang masih aktif kuliah berdasarkan keterangan siakad tahun masuk perguruan tinggi 2022-2024 sebanyak 120 orang mahasiswa. Adapun teknik pengambilan sampel menggunakan random sampling dan rumus slovin untuk menentukan banyaknya responden. Berdasarkan ketentuan tersebut sehingga jumlah sampel sebanyak 100 responden. Selanjutnya pada index massa tubuh menggunakan penghitungan berat badan dan tinggi badan dengan menggunakan rumus SBQ (Sendentary Behavior Quisioner) karangan (Adolphe Quetelet) analisis yang digunakan yaitu pearson che square. Hasil penelitian diketahui bahwa nilai Sendentary Behavior mahasiswa pendidikan jasmani memiliki nilai rata-rata keseluruhan sebesar 54 (sangat buruk) dan Index Massa Tubuh sebesar 26 (Gemuk).